2018
DOI: 10.1063/1.5029921
|View full text |Cite
|
Sign up to set email alerts
|

Structure and vibrational properties of the dominant O-H center in β-Ga2O3

Abstract: Hydrogen has a strong influence on the electrical properties of transparent conducting oxides where it can give rise to shallow donors and can passivate deep compensating defects. We have carried out infrared absorption experiments on H- and D-doped β-Ga2O3 that involve temperature- and polarization-dependent effects as well as relative H- and D-concentrations to probe the defect structures that hydrogen can form. The results of analysis of these data, coupled with detailed theoretical calculations, show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 42 publications
11
93
0
Order By: Relevance
“…To date, there have been several theoretical calculations predicting energy levels for acceptor-like gallium vacancies and donor-like oxygen vacancies that are close to the experimentally observed deep levels here. [35][36][37][38][39] Hydrogen-gallium vacancy complexes (i.e., V Ga -H, V Ga -2H) might also play a role since irradiation can affect the degree of H saturation of V Ga with different charge state transitions, (0/−1), (−1/−2), (−2/−3), etc., which has also been reported for proton-implanted β-Ga 2 O 3 with the V Ga -2H complex formation, 44 and possibly cause Frenkel pair generation. 39,45 Regarding the E C −4.48 eV state that remained unaffected after irradiation for both doses, this energy level is close to those that have been predicted for vacancies; 38,46 however, Note that the concentrations of the DLOS traps before and after irradiation are likely even greater (but at same ratio) than shown here due to their small optical cross sections causing an underestimation of these values.…”
Section: Article Scitationorg/journal/apmsupporting
confidence: 61%
“…To date, there have been several theoretical calculations predicting energy levels for acceptor-like gallium vacancies and donor-like oxygen vacancies that are close to the experimentally observed deep levels here. [35][36][37][38][39] Hydrogen-gallium vacancy complexes (i.e., V Ga -H, V Ga -2H) might also play a role since irradiation can affect the degree of H saturation of V Ga with different charge state transitions, (0/−1), (−1/−2), (−2/−3), etc., which has also been reported for proton-implanted β-Ga 2 O 3 with the V Ga -2H complex formation, 44 and possibly cause Frenkel pair generation. 39,45 Regarding the E C −4.48 eV state that remained unaffected after irradiation for both doses, this energy level is close to those that have been predicted for vacancies; 38,46 however, Note that the concentrations of the DLOS traps before and after irradiation are likely even greater (but at same ratio) than shown here due to their small optical cross sections causing an underestimation of these values.…”
Section: Article Scitationorg/journal/apmsupporting
confidence: 61%
“…[19,21]. These DFT results have also been utilized in recent β-Ga2O3 defect studies using electron spin resonance [37,38] and infrared spectroscopy [39,40] to attribute the presence of proton irradiation induced defects and implanted O-H bonds to the same point defect complexes.…”
mentioning
confidence: 91%
“…8-12 IR absorption peaks observed at 3437 cm À1 in annealed samples by Weiser et al 10 are attributed to a gallium vacancy decorated with two hydrogen atoms. Ritter et al 12 demonstrated that hydrogen-annealing of Ga 2 O 3 :Mg produced an IR peak at 3492 cm À1 , assigned to an O-H bond-stretching mode of a neutral MgH complex.…”
mentioning
confidence: 98%